Maxillary postimplantation syndrome: ocular aspects - A.O. Asmolova; O.V. Zborovska; O.E. Dorokhova; O.V. Pasechnik (Ukrainian Society of Ophthalmologists, 2018)
Background: Maxillary postimplantation syndrome (MPS) has been previously described as a complication occurring more than 1 year after maxillary implant placement in patients with partial loss of teeth due to accident, extraction and/or local periodontal disease. The syndrome is characterized by dental, rhinological, ocular and/or neurodental symptoms. Purpose: To determine frequencies of ocular disorders in patients who developed manifestations of maxillary postimplantation syndrome. Materials and Methods: Seventy four patients with MPS (age, 27 to 64 years) and 43 healthy volunteers (age, 25 to 63 years) were involved in the diagnostic study. Patients underwent a routine clinical examination including rhinoscopy, stomatoscopy, and paranasal sinus computed tomography. In addition, a routine eye examination was performed. Results: Ocular disorders were found in 81% of patients with MPS, and included functional injury of the nasolacrimal canal (51%), dacryocystitis (20.2%), and intermediate uveitis (6.7%) with complications manifesting as macular edema or epiretinal membrane (4.05%), optic nerve drusen (6.7%), and optic neuritis (5.4%). Some MPS patients exhibited several ocular disorders (including, in particular, a functional injury of the nasolacrimal canal or dacryocystitis). Conclusion: Ocular disorders were found in 81% of patients with MPS. Patients with MPS should undergo an eye examination even in the absence of ocular complaints.